Fair and Effective Policing Methods: Towards 'Good Enough' Policing - Bowling, Benjamin (Journal of Scandinavian studies in criminology and crime prevention, 2007)
It is unhelpful and unrealistic to demand perfect police; instead we should aim to achieve 'good enough' policing, re-evaluating and questioning the concepts of fairness and effectiveness. To be 'fair', should the police treat everyone identically or on the basis of their needs? To be effective, should the police be law-enforcers or guardians of community safety? How should we balance the tension between fairness and effectiveness? Do measures to increase fairness blunt police effectiveness, or is fairness an essential quality of effective policing? Focusing specifically on the power to stop and search people in public places and on the experiences of communities who complain of being 'over-policed and under-protected', this lecture ponders how 'good enough' policing can be achieved